Transdisciplinary Project Communication and Knowledge Sharing Experiences in Tanzania and Zambia through a One Health Lens - Bagnol, Brigitte; Clarke, Elizabeth; Li, Mu; Maulaga, Wende; Lumbwe, Hilda; McConchie, Robyn; de Bruyn, Julia; Alders, Robyn Gwen (Frontiers in Public Health, 2016)
The project “Strengthening food and nutrition security through family poultry and crop integration in Tanzania and Zambia” brings together animal, crop, and human health specialists, economists, ecologists, social scientists, and practitioners to work with participating communities. It aims to increase poultry value chain, crop farming systems efficiency, and household food and nutrition security and thus requires understanding of, and ability to work effectively within, complex systems. In this context, communication knowledge sharing and synthesis between stakeholders from diverse backgrounds and a range of experiences, perspectives, agendas, and knowledge is a challenge. To address this situation, communication is conceived as a dialog and a participatory process bringing together all stakeholders. This process results in unanticipated and unexpected results that require a high degree of flexibility and adaptability from team members. The paper analyses the approach and aim of the communication strategy developed for the project and the challenges faced.